Skeletal Class III malocclusion treated by pre-surgical orthodontics followed by bilateral sagittal split osteotomy (Bangladesh Journal of Orthodontics and Dentofacial Orthopedics, 2013)
Surgical correction of Dentofacial Deformities is the work of many surgeons but the orthodontist are very much involved in preparing the patients for surgery. This case report describes treatment for severe skeletal Class III with excessive reverse overjet by pre-surgical orthodontic treatment followed by bilateral sagittal split osteotomy (BSSO). The patient had a concave profile, a long lower facial height, large tongue volume and excessive mandibular protrusion and a high mandibular plane angle. The occlusion was well aligned including root paralleling in both the arches during the presurgical orthodontic treatment phase. After dental correction in both the arches, bilateral sagittal split osteotomy with mandibular push back was performed. The post treatment records showed a good facial profile and occlusion. The mandible was stable, however, there was spacing in the upper anterior segment. These results demonstrate that presurgical orthodontic treatment combined with bilateral sagittal split osteotomy resulted improvement of facial profile, aesthesis and functional need. DOI: http://dx.doi.org/10.3329/bjodfo.v1i2.15984 Ban J Orthod & Dentofac Orthop, April 2011; Vol-1, No.2, 9-12